Administrative Analysis on Value Added Tax in Electronic Wallet Industry in Indonesia (Study Case At PT. MLH) - Mohamad Luhur Hambali; Milla S Setyowati (Integrated Journal of Business and Economics (IJBE), 2020)
The development of the industry continues to develop over time. One of the developing industries in Indonesia is the Digital Wallet Financial Technology Industry. This study goal is to analyze the administration of Value Added Tax in the electronic wallet financial technology industry in Indonesia, by taking a case study at one of the fintech companies which affiliated to the Indonesian State-Owned Enterprises in Indonesia. By using qualitative research methods and in-depth interview data collection techniques and literature studies, this research are to be able to analyze and describe alternative on Value Added Tax administration policies that are appropriate for the electronic wallet financial technology industry in Indonesia.